The Role of Whole Exome Sequencing in Distinguishing Primary and Secondary Lung Cancers - Vokes NI (Dove Medical Press, 2021)
Natalie I Vokes,1,2 Jianjun Zhang1,2 1Department of Thoracic and Head and Neck Oncology, University of Texas MD Anderson Cancer Center, Houston, TX, USA; 2Department of Genomic Medicine, University of Texas MD Anderson Cancer Center, Houston, TX, USACorrespondence: Natalie I Vokes; Jianjun Zhang Email nvokes@mdanderson.org; jzhang20@mdanderson.orgAbstract: Non-small cell lung cancer (NSCLC) that presents with multiple lung tumors (MLTs) poses a challenge to accurate staging and prognosis. MLTs that arise as clonally related secondary metastases from a common primary are higher stage and often require adjuvant chemotherapy or may in fact be incurable stage IV lesions. Conversely, MLTs that represent distinct primaries have a better prognosis and may be overtreated if inappropriately classified as related secondaries. Historically, pathologic and radiographic criteria were used to distinguish between primary and secondary MLTs; however, the advent of genomic profiling has demonstrated limitations to these historic classification systems. In this review, we discuss the use of molecular profiling to distinguish between primary and secondary lung cancers, with a focus on the insights gleaned from whole exome sequencing (WES) analyses. While WES is not yet feasible in routine clinical practice, WES studies have helped elucidate the clonal relationship between primary and secondary lung cancers and provide important context for the application of targeted sequencing panel-based analyses.Keywords: genomics, non-small cell lung cancer, metastasis